ANALYSIS OF VILLAGE FUND MANAGEMENT IN POTUGU VILLAGE, MOMUNU DISTRICT, BUOL REGENCY, SULAWESI TENGGAH PROVINCE - Agus, Ramli; muhammad, Ikram; Rauf, Nuzmerini (Jurnal Ilmu Manajemen dan Bisnis, 2025)
This study aims to analyze the management of village funds in Potugu village, Momunu District, Buol Regency. This type of research uses a qualitative method with case studies or field studies. Data collection techniques by observation, interviews and documentation. The results of the study show that planning in potugu village is carried out through village deliberations involving various elements of society. In this process, it is hoped that every proposal from residents can be considered, community participation in planning is still low. This is due to the lack of public understanding of the importance of village fund planning, so that some of the proposed programs do not fully reflect the urgent needs.